Female genital cosmetic procedures from the perspective of health practitioners: a systematic review of knowledge, attitude and practice studies - Elham Azmoude; Samira Ebrahimzadeh Zagami; Elahe Hooshmand; Elham Taheri; Nahid Jahani Shoorab (BMC, 2024)
Abstract Background Currently, the popularity of female genital cosmetic procedures is on the rise worldwide. Despite the multiple roles of healthcare practitioners at different stages of women's decision-making for these procedures, limited studies have been conducted in this area. This systematic review aimed to summarize the available qualitative and quantitative data from observational studies that investigated healthcare practitioners' knowledge, attitudes and practices regarding female genital cosmetic procedures. Method The present systematic review was performed based on PRISMA guidelines. All published studies that examined the knowledge, attitudes and practices of healthcare practitioners regarding female genital cosmetic procedures were included. PubMed/Medline, Scopus, Web-of-science, ScienceDirect and Google Scholar were searched using related keywords until 30 November 2023. Quality assessment was performed using the Appraisal Tool for Cross-Sectional Studies and Checklist for Qualitative Research from the Joanna Briggs Institute. Results Eight studies comprising 2063 healthcare practitioners met the inclusion criteria and were analysed. Based on the results, some healthcare practitioners in the included studies acknowledged the naturalness of the variety of female genitalia, but others considered very small labia as attractive. There was little agreement on the positive effects of female genital cosmetic procedures on improving women's quality of life and sexual function in the included studies. Nearly all healthcare practitioners have seen women who had concerns about being natural of their genitalia. Meanwhile, approximately two-thirds of them had encountered women requesting female genital cosmetic procedures. Only three-quarters of healthcare practitioners felt confident in assessing the normality of genital appearance. The willingness to perform female genital cosmetic procedures was higher among male healthcare practitioners and plastic surgeons than among females and gynecologists. Conclusion The results indicated that although a large number of healthcare practitioners had encountered women who were concerned about genitalia or requested genital cosmetic procedures, they did not have sufficient knowledge or favorable attitudes and practices in most related fields. Therefore, it is recommended to design educational interventions, formulate guidelines and make policies.